Privacy, probity and public interest - Whittle, S; Cooper, G (Reuters Institute for the Study of Journalism, Department of Politics and International Relations, University of Oxford, 2009)
In Britain there is currently a battle engaged around the point at which freedom of information and expression meet the right to the protection of private life. Yet neither ‘private life’ nor ‘public interest’ are immutable. There have been significant changes in how both have been perceived and defined over time. This report aims to address some of the questions over the changing nature of privacy, which private matters can be revealed by journalists in the public interest and whether the increasing use of the Human Rights Act to safeguard an individual’s privacy is creating a ‘chilling’ effect on journalism. The authors interviewed lawyers, academics, journalists, bloggers and those who have found their privacy invaded by the media—as well as those who have invaded it themselves.